IMPLEMENTASI PEMBELAJARAN STEAM PADA MATERI IPA UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Khairunnisa, Rahma; Sheryl Mutiara Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science learning at the elementary school level often faces challenges in fostering students’ learning interest. Conventional methods that rely on memorization are considered less effective in cultivating curiosity and active engagement. The STEAM approach emerges as an innovative solution by integrating multiple disciplines in a contextual and project-based manner. This study aims to examine the implementation of STEAM-based learning in elementary science education to enhance students’ learning interest, as well as to identify the challenges in its application. This review employs a qualitative method using a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. Data were obtained from 20 national and international scholarly articles published between 2020 and 2025 that met inclusion criteria: focusing on STEAM implementation in science learning, containing empirical data, and being fully accessible. The results indicate that STEAM is effective in increasing learning interest through creative, collaborative, and experience-based learning activities. Students became more active, motivated, and demonstrated a deeper understanding of science concepts. However, challenges such as limited teacher training, inadequate infrastructure, and curriculum readiness remain significant obstacles. Therefore, improving teacher competencies, developing flexible curricula, and providing adequate facilities are essential efforts to optimize STEAM implementation in elementary schools. This review is limited by its scope and publication range, thus further research with broader and deeper exploration is recommended.